Prevalence of asthenopia among computer operators in Central India and effectiveness of educational intervention - Arshad, Shoaib; Khan, Amreen; Pal, D. K.; Melwani, Veena; Verma, Shipra; Sawlani, Harshima (International Journal Of Community Medicine And Public Health, 2019)
Background: Objective was to study the prevalence of asthenopic symptoms among computer operators in central India and assess the change in their practices related to factors affecting asthenopia symptoms and relief measures.. Methods: Longitudinal Educational Interventional Study, done on 150 employees of computer based company offices of Bhopal city in duration of 3 months from August 2018 to October 2018 after obtaining Ethical clearance from the institutional ethics committee and they were asked to fill a pre-tested questionnaire, after obtaining their verbal consent. Other relevant information was obtained by personal interview and inspection of their working area. The data was entered in MS excel and analysis was done using Epi-info 7 software. Results: Among the 150 participants studied, the overall prevalence of asthenopia (at least 1 symptom present) is 87.3%. The prevalence of various asthenopic symptoms varied from 85.3% (eye fatigue) to 18.7% (blurring of vision). With educational intervention, significant change was observed in symptoms and relief measures. Conclusions: Prevalence of asthenopia was found to be quite high in computer operators, especially in those who started its use at an early age. Individual as well as work-related factors were found to be associated with asthenopia.